Faktor-Faktor yang Berhubungan dengan Perilaku Pengelolaan Sampah Rumah Tangga pada Ibu Rumah Tangga di Sekitar Tempat Pembuangan Akhir Rawa Kucing Kota Tangerang Tahun 2025 - Ahda Ahda; Ernyasih Ernyasih; Andriyani Andriyani; Munaya fauziah; Fini Fajrini (Journal of Educational Innovation and Public Health, 2026)
Background: Waste management remains one of the environmental issues requiring serious attention, particularly in the area surrounding the Rawa Kucing Final Disposal Site (TPA), Tangerang City. Although the Rawa Kucing Final Disposal Site has implemented a controlled landfill system, waste management practices in the surrounding residential areas remain far from optimal. Objective: This study aims to identify the factors associated with waste management among housewives living around the Rawa Kucing Final Disposal Site (TPA) in 2025. Methods: This study employed a cross-sectional design with univariate and bivariate analyses. Data were collected through questionnaires distributed to housewives residing around the Rawa Kucing Final Disposal Site. The variables examined included age, education, income, knowledge, attitudes, the availability of facilities and infrastructure, and the waste management behavior of housewives. Results: The findings revealed that age, education, knowledge, and attitudes significantly influenced the waste management behavior of housewives. Housewives with higher educational attainment, better knowledge, and more positive attitudes toward health tended to demonstrate better waste management behavior. Conclusion: Age, education, knowledge, and attitudes were found to significantly influence the waste management behavior of housewives.